Presentation and surgical management of a superficial temporal artery pseudoaneurysm: A case report. (February 2021) - Muir, Hannah; Cowan, Kirsty; Steele, Peter; Downie, John Jeff
Highlights: Raise awareness of pseudoaneurysms as an uncommon but important differential diagnosis for masses in the head and neck region. Highlight the importance of excluding pseudoaneurysm prior to diagnosing a simple post traumatic haematoma. Discuss treatment strategies for superficial temporal artery pseudoaneurysms. Abstract: Introduction and Importance: A Superficial Temporal Artery Pseudoaneurysm is an uncommon, but important, differential diagnosis for masses in the head and neck region. This work has been reported in line with SCARE 2020 criteria [1 ]. Case Presentation: An 81-year-old male presented to the Oral and Maxillofacial Department with a facial swelling that had been present for a duration of three weeks. A provisional diagnosis of a haematoma was made and an ultrasound carried out to confirm diagnosis. Ultrasonography and CT Angiography confirmed a pseudoaneurysm arising from the left superficial temporal artery. Clinical Discussion: Although this is a relatively uncommon diagnosis it is important to be aware of the key diagnostic tools used to identify a pseudoaneurysm. Specifically, their potential to exclude a pseudoaneurysm prior to diagnosing a simple post-traumatic haematoma. This is important as the treatment strategies for the two pathologies differ considerably. Useful learning points from this case include diagnostic aids such as the unique pulsatile nature of the mass and the role of ultrasonography and CT Angiography in confirming diagnosis and guiding surgical management. Conclusion: Pseudoaneurysms are an important consideration as a differential diagnosis of masses in the head and neck region. This case report may impact upon management of future similar cases by highlighting significant aspects of their clinical diagnosis and surgical management, enabling early identification and appropriate management.